Promoting college and career readiness among underserved adolescents: A mixed methods pilot study. (19th June 2021) - Gee, Kevin A.; Beno, Carolynne; Lindstrom, Lauren; Lind, John; Gau, Jeff; Post, Cindy
ABSTRACT: Introduction: Many underserved adolescents, defined as those with inequitable access to educational resources, face limited access to interventions that develop their college and career know‐how. In our study, we implemented and evaluated a pilot college and career readiness curriculum intervention called Paths to the Future for All (P2F4A). P2F4A takes a developmental approach to college and career development, weaving together the procedural know‐how of college and career planning with a broader focus on building social‐emotional skills that support positive trajectories towards the future. We evaluated pre‐post changes in adolescents' career‐related and social‐emotional outcomes alongside views of their personal growth. Methods: We used a purposeful sample of five schools in the Western region of the United States and recruited a sample of adolescents ( N  = 61; M age  = 16.3 years; 57.4% female) who experienced challenging academic and life circumstances to participate in P2F4A. We conducted pre‐post surveys as well as focus groups and interviews with adolescents. Results: We detected significant ( p  < .05) pre‐post gains in adolescents' knowledge of P2F4A curricular content and selected coping skills, such as relaxing and solving family problems. Our focus groups and interviews revealed that P2F4A helped adolescents build stronger interpersonal relationships with peers and the content was directly applicable to real life. Conclusion: Our new findings suggest that college and career readiness curriculum interventions—if appropriately developed for and targeted to underserved adolescents—have strong potential to build underserved adolescents' foundational skills that they can apply towards realizing their future college and career aspirations.